The Impact of Space Economy in Creating Value to the Spacefaring Nations’ Economies - Al Hubaishi, Hajar (Advances in Social Sciences Research Journal, 2026)
The Space Economy could be defined as, the full range of activities and the use of resources by human beings in the course of exploring space, to make new applications in economic areas, such as meteorology, energy, telecommunications, insurance, transport, maritime, aviation and urban development, leading to additional socio-economic benefits. Some analysts argued that the ongoing emerging space industry could mushroom grow and become a trillion-dollar industry by 2040.